أهم التغيرات البدنية التي طرأت على عناصر اللياقة البدنية لدى لاعبي كرة القدم الحديثة - زيزفون فادي (Latakia University Journal -Medical Sciences Series, 2013)
في هذا البحث تمّ الاستعانة بعينة من مدربي فرق كرة القدم من الدرجة الأولى في الدوري السوري (20 مدرب) وذلك لتقييم مدى معرفة هؤلاء المدربين بالتغيرات البدنية التي طرأت على عناصر اللياقة البدنية لدى لاعبي كرة القدم الحديثة, كما تناولت الدراسة تحليل وتقييم هذه التغيرات خلال السنوات الأربعين الأخيرة من خلال تحليل شامل للأبحاث والدراسات العلمية, وهذا من شأنه مساعدة المدربين في الانتباه إلى هذه القدرات خلال مراحل التدريب المختلفة بهدف البناء المثالي لها بما يتناسب مع متطلبات المنافسة. أظهرت نتائج الدراسة عدم قدرة المدربين على التمييز بين القدرات البدنية وأشكال ظهورها, مما يدل على عدم معرفتهم بالمعلومات الأساسية لهذه التغيرات. هناك العديد من التغيرات البدنية نذكر منها: 1. المسافة الكلية المقطوعة 8-12 كم و تقدر نسبة الزيادة في المسافة المقطوعة حوالي 10% سنويا حتى عام 1985 و ثبات ملحوظ منذ عام 1985 و حتى 2010 2. تتراوح حركات الجري المنفذة بالسرعة القصوى من 0 إلى 5 م 3. الحركات الخاصة بكرة القدم بين 40-100 حركة (وثب – تسديد كرة – زحلقة و 1 ضد 1) 4. اختلاف متطلبات كل صفة من هذه الصفات بحسب مركز اللاعب و المهمة التكتيكية المنوطة به. In this research a sample of soccer coaches from the first class in the Syrian League soccer (20 coaches) were used to get a real evaluation of their knowledge and awareness about the physical changes that have occurred on the fitness elements of modern soccer players. The modern physical changes in soccer play were also analyzed and estimated for the last forty years depending on a comprehensive analysis of the scientific researches and studies specialized in this field. This would assist coaches to take attention to these capabilities through the different stages of training in order to make them in a perfect construction in line with the requirements of competition. The Results showed that the coaches could not distinguish between modern physical changes and their manifestation or appearance forms, which refers to lack of their information and familiar about these changes. There are many physical changes such as: The total distance of 8-12 Km which estimated by 10% annually until 1985 and a remarkable constancy since 1985 until 2010 Running movements performed by a maximum speed ranging from 0 to 5 m Soccer movements from 40-100 movement (jump- Tackling- shot ball and 1 vs. 1) Requirements of each property differ according to the player position and the tactical task entrusted to him.